The Effect of Customer Experience, Customer Value and Customer Satisfaction on Grab Online Transportation Customer Loyalty on South Jakarta National University Students - Jihan Fahima; Resti Hardini; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
This study aims to analyze the effect of customer experience, customer value and customer satisfaction on customer loyalty for Grab Online Transportation at the National University of South Jakarta. The research method used in this study is a descriptive quantitative method with a population of South Jakarta National University students who use Grab Online Transportation. There were four variables studied in this study, namely Customer Experience (X1), Customer Value (X2) and Customer Satisfaction (X3) as independent variables, and Customer Loyalty (Y) as the dependent variable. This study used a sample of 96 respondents. The technique used in this research is non-probability sampling with purposive sampling. This study uses primary data collected through questionnaires which are processed using multiple linear regression and hypothesis testing on the IBM SPSS 25.0 application. The results of the study based on the t-test showed that customer experience (X1) had a positive and significant influence on customer loyalty, this can be seen from the results of the t-test where tcount > ttable (2.823 > 1.984) and significance (0.006 < 0.05). Customer value (X2) has a positive and significant effect on customer loyalty, this can be seen from the results of the t-test where tcount > ttable (2,013 > 1,984) and significance (0,047 < 0,05). Customer satisfaction (X3) has a positive and significant effect on customer loyalty (Y), this can be seen from the results of the t test where tcount > ttable (4,420 > 1,984) and significance (0,00 < 0,05). Thus, it can be concluded that the variables of customer experience, customer value and customer satisfaction have a positive and significant effect on customer loyalty.